Multi-Temporal Photogrammetric Analysis to Monitoring the River Las Minas, Punta Arenas, Chile - Koschitzki, R.; Schwalbe, E.; Kroehnert, M.; Cardenas Mansilla, Carlos Alberto; Maas, H-G. (My University, 2018)
This paper presents a multi-temporal photogrammetric model of analysis to monitoring of the Rio de Las Minas basin, located near to Punta Arenas city in southern Chile, this basin is constantly in danger, for landslide risks that can block and dam the river, and as a result probably catastrophic flood. To prevent such landslide-triggered hazards, the paper focuses on photogrammetric landslide detection and analysis using multi-temporal aerial images to reliably detect major geomorphological changes. As example, with datasets from 2014 and 2015 of the river Las Minas, two points clouds were generated to analyze landslides by means of the height differences between both clouds, which allowed establishing an autonomous model to detect landslides through the use of UAV's. Finally, recommendations are presented about the data acquisition system, its georeferencing and the monitoring plan by mean of UAV's.
Keywords: uav; monitoring; flooding; photogrammetry; sfm